Operational use of electronic records in police work - Erik Borglund (Information Research: An International Electronic Journal)
Introduction. This research is about how police officers use electronic records in their operational work, reacting to calls from the dispatch centre. Method. Three different qualitative studies, involving interviews and observations, were used to collect data. The studies were performed at a police county in the north of Sweden during 2003. Analysis. The empirical data were analysed using a hermeneutical analysis technique without computer-based support. Iterative analysis was performed, where empirical data related to the use of electronic records were identified and grouped together into larger categories, which were named descriptively. Results. There is a widespread use of information retrieved from electronic records. This has changed the possibilities for police officers to get reliable and authentic information for both tactical and legal decisions, which increases the officers' ability to make correct decisions within operational work. Information technology and information systems now handle many administrative tasks, and allow access to and searching of electronic information independently of the physical location of the officer. This opens up a possibility for mobile access to trustworthy information that supports police work. Conclusion. Operational police work has changed in a positive direction by the use of electronic records, and it is possible to develop this change even further. Record management systems designed to support access independent of physical location of the police officer could open up new possibilities for working police officers.